Нові палеоантропологічні рештки на Гірському Тікичі - Гладких, М.І.; Рижов, С.М.; Суховий, М.О. (Археологія, 2002)
У статті описано рештки практично повного скелета людини пізньопалеолітичного віку. Впервые на территории Украины (Черкасская обл.) обнаружены остатки практически полного скелета позднепалеолитического возраста. Предварительная радиокарбонная датировка (12 600 +(−) 90) лет назад. For the first time in the territory of Ukraine (the Cherkasy region), the remains of almost the entire skeleton of the Upper Paleolithic time are found. The preliminary radiocarbon dates from 12,600 +(−) 90 years ago.